Understanding the Accessibility of Urban Parks and Connectivity of Green Spaces in Single-Person Household Distribution: Case Study of Incheon, South Korea - Kichan Kim; Chang Kil Lee; Hyun Woo Kim (Land, 2022)
Given the rapidly increasing need for policies with regard to single-person households in Korea, this study examines the effects of park accessibility and the connectivity of green spaces on the spatial distribution of single-person households. SK-Tmap API and Conefor 2.6 are used to analyze park accessibility and green space connectivity, respectively. Multiple and spatial regression analyses are conducted using variables for the following three characteristics: park and green space, housing, and region. The findings show that generalized Betweenness Centrality–Integral Index of Connectivity based index (dBC_IIC), apartments, studio apartments, housings larger than 85 m2, distance to welfare facilities, and population density had a positive association with the spatial distribution of single-person households, while park accessibility, difference in Number of Links (dNL), generalized Betweenness Centrality–Probability of Connectivity based index (dBC_PC), and housing sale prices had a negative relationship. Regression analyses are further conducted for different age groups (10–20 years, 30–50 years, and over 60 years). In terms of park connectivity, dBC_PC showed a negative effect and dBC_IIC had a positive effect for the 10–20 age groups, while the 30–50 age group showed the same result as that of all single-person households. For single-person households over 60 years of age, no connectivity index was found to be significant. Policy implications are made in the short- and mid- to long-term for strengthening the connectivity of parks and green spaces in the study area. The results of this study can be used as an important guideline for establishing park and green space plans in consideration of single-person households in the future.